Pentingnya Komunikasi Intra Personal Dalam Menentukan Makna Hidup (Studi Kasus: Mahasiswa Prodi Bimbingan Penyuluhan Islam UIN Syarif Hidayatullah Jakarta) - Zannuby Al Izzami; Nasichah Nasichah; Eryanti Widya Cahyaningrum; Kurnia Farhanah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
As it is known that intrapersonal communication is very important in determining the meaning of one's life. In living life, a person will certainly be faced with various kinds of situations that require decision making. Through good intrapersonal communication, one can develop introspection and self-reflection. Which allows a person to better understand himself, and evaluate himself from various aspects such as values, needs, motivations, and goals in life. Thus, a person can find the meaning and purpose of life that is appropriate and also commensurate with himself. The purpose of writing this research is to reveal how important the role of intrapersonal communication is in determining the meaning of life. The method used in this study is qualitative research, with data collection through interviews. This study involved 5 (five) informants, namely students of the Islamic Counseling Guidance Study Program who were chosen deliberately by researchers according to the objectives and needs of the research. Based on the findings of this study, the majority of students who became informants stated that intrapersonal communication has an important role in determining the meaning of one's own life.